Education performance of Chandauli district: analyzing progress through aspirational district metrics - Arti Verma; Seema Tiwari (National Geographical Journal of India, 2025)
The Aspirational District Programme (ADP), launched by the Government of India in 2018, aims to transform underdeveloped districts through focused development efforts, with education being a key priority area. This study analyses the educational status of the Chandauli district in Uttar Pradesh by assessing progress across critical educational indicators under the ADP framework. Secondary data were obtained from Census 2011, U-DISE+ 2021–22, and the National Achievement Survey (NAS) 2021. School infrastructure indicators include the availability of functional toilets, safe drinking water, electricity, and adequate classroom facilities. Enrolment and retention focus on trends in student enrolment, transition rates between educational levels, and dropout rates. Learning outcomes assess student performance in language, mathematics, and science across different grade levels. Digital literacy evaluates access to the internet and computer laboratories in schools. Teacher–student ratio and quality consider pupil–teacher ratios at various stages of education, as well as teachers’ training and professional qualifications. Descriptive statistical methods were employed to analyze the data. The findings indicate that Chandauli has shown notable progress in terms of school infrastructure and basic amenities. However, issues such as declining transition rates, high dropout levels in the secondary stage, poor digital infrastructure, and significant gender gaps in literacy persist. Learning outcomes tend to decline as students advance to higher grade levels, underscoring the need to strengthen foundational learning and enhance the quality of teaching. Despite fluctuations in district rankings and composite scores, the ADP has provided a framework for measurable improvement. To achieve sustained educational growth, Chandauli necessitates targeted policy interventions that emphasize digital access, gender parity, and teacher development. These measures are essential for addressing existing gaps and promoting inclusive development.